A New Curve of Critical Leaf Potassium Concentration Based on the Maximum Root Dry Matter for Diagnosing Potassium Nutritional Status of Sweet Potato - Lv, Zunfu; Lu, Guoquan (Frontiers in Plant Science, 2021)
Critical leaf nutrient concentrations have often been used to diagnose the nutritional status of crops. Determining critical leaf K concentrations for the maximum root dry matter (RDM) will provide a reliable means of linking leaf K nutrient concentrations to the yield of sweetpotato. Three field experiments, using varying K application rates (0–300 kg K ha–1) and two sweetpotato cultivars were performed in Zhejiang province of China. A new critical leaf K curve (Kleaf) based on the maximum RDM were determined to assess K nutrition in sweetpotato and described by the equation K_leaf=4.55×R〖DM〗_max^(–0.075). A critical root K curve (Kroot) based the maximum RDM were also determined to assess K nutrition and described by the equation K_root=2.36×R〖DM〗_max^(–0.087). The K nutrition index (KNI) were constructed to identify the situations of K-limiting and non-K-limiting treatments. The leaf K nutrition index (KNIleaf) ranged from 0.56 to 1.17, and the root K nutrition index (KNIroot) ranged from 0.52 to 1.35 during sweetpotato growth period. The results showed that the critical leaf K concentration curve can be used as an accurate leaf K status diagnostic tool at critical growth stages that connected leaf nutrient concentration and sweetpotato tuber yield. This K curve will contribute to K management of sweetpotato during sweetpotato growth period in China.